Safety of a prehospital emergency medical services protocol for an alternative destination for pediatric behavioral emergencies in Alameda County. Issue 2 (9th April 2023) - Glomb, Nicolaus W.; Trivedi, Tarak; Grupp‐Phelan, Jacqueline; Schriger, David L.; Sporer, Karl
Abstract: Background: Pediatric patients with behavioral health emergencies (BHEs) are often transported to an emergency department (ED) by emergency medical services (EMS), despite having no physical medical complaints, to await psychiatric evaluation and treatment. This process leads to significant delays in their care. We examined the safety of directly transporting pediatric patients with BHEs from the field to an alternative destination of a psychiatric emergency service (PES) facility using an EMS protocol. Methods: A retrospective review from November 1, 2011, to November 1, 2016, was conducted for pediatric EMS encounters using EMS data from Alameda County, California. Our primary outcome was the safety of a prehospital alternative destination protocol. We identified the proportion of patients who required retransport to an ED within 24 h after arriving at PES (defined as a failed diversion). We also describe the mortality of all patients being transported for a BHE. Results: There were 38, 241 total pediatric encounters, with 20.1% for BHEs. A total of 3122 (41%) BHE encounters met protocol criteria and were transported directly to the PES. Only 16 (0.5%) patients had a secondary transport (failed diversion) to an ED within 24 h of arrival. No patients with a BHE transported to the PES died within 30 days of the EMS encounter. Conclusion: Death and adverse clinical outcomes are extremely rare in pediatric patients using a prehospital alternative destination protocol. This information could significantly improve the care of children with BHEs.